Is it a challenge or a threat?: A dual-process model of teachers’ cognition and appraisal processes during conceptual change - Gregoire, Michele (Educational psychology review, 2003)
What accounts for well-meaning teachers’ lack of implementation of subject-matter reforms, such as making one’s classroom centered on problem solving, even when they positively value the reform and believe they are implementing it in their classrooms? Teachers’ subject-matter beliefs may constrain them from adopting practices that conflict with those beliefs. The purpose of this article is to propose a theoretical model, the Cognitive–Affective Model of Conceptual Change, that integrates key findings from overly cognitive models of belief change with motivational and affective factors found in social psychology theory and research. This model explains why teachers’ beliefs about instruction are resistant to reforms that challenge their existing beliefs, and it provides a conceptual framework within which to devise a better means of advancing teachers’ beliefs and supporting them in the process of implementation. (Orig.).